Characterization of a bacterial copper‐dependent lytic polysaccharide monooxygenase with an unusual second coordination sphere. (24th January 2020) - Munzone, Alessia; El Kerdi, Bilal; Fanuel, Mathieu; Rogniaux, Hélène; Ropartz, David; Réglier, Marius; Royant, Antoine; Simaan, A. Jalila; Decroos, Christophe
Abstract : Lytic polysaccharide monooxygenases (LPMOs) are copper‐dependent enzymes involved in the degradation of recalcitrant polysaccharides such as cellulose or chitin. LPMOs act in synergy with glycoside hydrolases such as cellulases and chitinases by oxidatively cleaving a number of glycosidic bonds at the surface of their crystalline substrate(s). Besides their role in biomass degradation, some bacterial LPMOs have been found to be virulence factors in some human and insect pathogens. Photorhabdus luminescens is a nematode symbiont bacterium that is pathogenic to a wide range of insects. A single gene encoding a LPMO is found in its genome. In this work, we report the characterization of this LPMO, referred to as Pl AA10. Surprisingly, Pl AA10 lacks the conserved alanine residue (substituted by an isoleucine) found in the second coordination sphere of the copper‐active site in bacterial LPMOs. Pl AA10 was found to be catalytically active on both α‐ and β‐chitin, and exhibits a C1‐oxidation regiospecificity, similarly to other chitin‐active LPMOs. The 1.6 Å X‐ray crystal structure confirmed that Pl AA10 adopts the canonical immunoglobulin‐like fold typical for LPMOs. The geometry of the copper‐active site is not affected by the nearby isoleucine, as also supported by electron paramagnetic resonance. Nevertheless, the bulkier side chain of isoleucine protrudes from the substrate‐binding surface. A bioinformatic study on putative bacterial LPMOs unveiled that they exhibit some variability at the conserved active‐site alanine position with a substitution in about 15% of all sequences analyzed. Database: Structural data (atomic coordinates and structure factors) reported for Pl AA10 are available in the Protein Data Bank under accession number 6T5Z . Enzymes: Pl AA10, EC1.14.99.53 . Abstract : Pl AA10 – a bacterial copper‐dependent lytic polysaccharide monooxygenase (LPMO) from Photorhabdus luminescens – harbors an unusual active‐site alanine‐to‐isoleucine substitution. Notwithstanding, Pl AA10 is active on α‐ and β‐chitin. The isoleucine side chain does not directly influence the copper ion geometry but protrudes from the substrate‐binding surface. A bioinformatic analysis revealed that, similarly to Pl AA10, 15% of bacterial LPMOs lack the conserved alanine.